2017
DOI: 10.1155/2017/4792932
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone Administration Following Spinal Cord Injury Reduces Aquaporin 4 Expression and Exacerbates Edema

Abstract: Spinal cord injury (SCI) is an incapacitating condition that affects motor, sensory, and autonomic functions. Since 1990, the only treatment administered in the acute phase of SCI has been methylprednisolone (MP), a synthetic corticosteroid that has anti-inflammatory effects; however, its efficacy remains controversial. Although MP has been thought to help in the resolution of edema, there are no scientific grounds to support this assertion. Aquaporin 4 (AQP4), the most abundant component of water channels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
(44 reference statements)
1
37
0
1
Order By: Relevance
“…These results suggested that the increased coexpression and expression levels of AQP4 and Kir4.1 might be involved in the formation of medullospinal edema and the induction of pathological changes in medullospinal tissues, as part of secondary ASCI; the inhibitory effects of MP on medullospinal edema might be associated with its reduction of the coexpression and expression levels of AQP4 and Kir4.1. Recent study demonstrated that MP administration following SCI reduced AQP4 expression and exacerbates edema 24 . The Cabrera-Aldana's 24 study showed that SCI increased AQP4 expression in the spinal cord white matter and that MP diminished such increase to baseline levels.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These results suggested that the increased coexpression and expression levels of AQP4 and Kir4.1 might be involved in the formation of medullospinal edema and the induction of pathological changes in medullospinal tissues, as part of secondary ASCI; the inhibitory effects of MP on medullospinal edema might be associated with its reduction of the coexpression and expression levels of AQP4 and Kir4.1. Recent study demonstrated that MP administration following SCI reduced AQP4 expression and exacerbates edema 24 . The Cabrera-Aldana's 24 study showed that SCI increased AQP4 expression in the spinal cord white matter and that MP diminished such increase to baseline levels.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is among the serious nervous system disorders characterized by complete or partial damage to motor function resulting in movement loss . Efforts are being continuously made to develop better treatment strategies for SCI . Each year around 20 to 40 people suffer from SCI in every one lakh people globally .…”
Section: Introductionmentioning
confidence: 99%
“…Each year around 20 to 40 people suffer from SCI in every one lakh people globally . The common causes responsible for SCI include sports injuries, fall from long distances and traffic accidents . The traffic accidents account for around 45% SCI cases in United States, fall from high altitudes for 17% and sports injuries for 12% .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of MP is highly controversial owing to non-reproducibility of its beneficial effects as well as unwanted side effects (Evaniew et al, 2016;Liu et al, 2017;Shroff & Gupta, 2015). The American Association of Neurological Surgeons in their guidelines no longer recommend MP usage for the management of acute SCI (Cabrera-Aldana et al, 2017). In view of this, drug for SCI is, presently, an important research study for clinicians and scientists.…”
Section: Introductionmentioning
confidence: 99%